Phenotypic detection of Extended Spectrum Beta lactamase production from E. coli and K. pneumoniae in urinary samples among children (Tribhuvan University Journal of Microbiology, 2020)
Objectives: The main objective of this study was to detect antimicrobial drug resistance (AMR) and Extended Spectrum Betalactamase (ESBL) production phenotypically in E. coli and K. pneumoniae isolated from urines with significant bacteriuria.Methods: This cross-sectional study was carried out in Microbiology laboratory of Kathmandu College of Science and Technology, Kamalpokhari. The urine samples from suspected urinary tract infected cases were collected from both genders of children below 15 years of age from Out and In-patient department of International Children Friendship Hospital, Maharajgunj and those with significant bacteriuria were cultured for isolating the bacterial etiology targeted as E. coli and K. pneumoniae. AMR for these two bacteria were tested and detected using Kirby Bauer Disc Diffusion technique. ESBL production was confirmed by Double Disc Synergy test (DDST) and Phenotypic Confirmatory Disc Diffusion Test (PCDDT) after screening for all the isolates showing resistance to third generation cephalosporin namely Cefotaxime and Ceftriaxone according to CLSI instructions.Results: Out of 388 urine samples processed, 29.89% (116/388) showed significant bacterial growth. Five (5) different Aerobic Gram Negative bacterial species were detected and identified. E. coli topped the list (70.68%) followed by K. pneumoniae (15.52%), K. oxytoca (8.62%), Proteus vulgaris (3.45%) and Pseudomonas aeruginosa (1.73%). Among positively screened (44.82%) beta lactamase producers (36.2%) of total isolates were confirmed to produce ESBL. Among ESBL producing isolates, highest susceptibility was seen to Ceftazidime (23.80%) followed by Cefotaxime (16.67%). The ESBL producing isolates were least susceptible to Ceftriaxone (2.38%). AMR was detected using Kirby- Bauer Disc diffusion technique. Comparatively less resistance to amikacin and nitrofurantoin (19.1% and 9.53% respectively) was seen among ESBL producers. 40 out of the 42 (95.23%) ESBL producing strains showed susceptibility to the combination drug, piperacillin/tazobactam. The resistance to meropenem was observed to be less (9.53%) as compared to that to imepenem (7.15%).Conclusion: This study concluded that there is high prevalence of multidrug resistant uropathogenic clinical strains of E. coli and K. pneumoniae with higher rates of ESBL production. A resistance to the carbepenems is also emerging. Appropriate antimicrobial regimen selection for empirical therapy is thus important for such cases. On managing the empirical antibiotics practice, one can reduce the risk of ESBL producers. There is an essence need of regular routine practice of ESBL detection.